2022
DOI: 10.1016/j.jmb.2021.167438
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Control of Human Coronavirus Infection and Viral Evasion: Mechanistic Insights and Implications for Antiviral Drug and Vaccine Development

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 240 publications
(259 reference statements)
1
7
0
1
Order By: Relevance
“…It was observed that several ISGs, like APOL2, RAB27A, FAM46A, and FAM46C that inhibited SCoV-2 replication, also inhibited HCoV-229E replication. However, other ISGs like SQLE, SLC1A1, and STARD5, which were found to potentially inhibit HCoV-229E, were not found to inhibit SCoV-2 (Zhao et al, 2022 ). These studies demonstrated overlap in ISG-mediated inhibition mechanisms of SCoV-2 and HCoV-229E replication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that several ISGs, like APOL2, RAB27A, FAM46A, and FAM46C that inhibited SCoV-2 replication, also inhibited HCoV-229E replication. However, other ISGs like SQLE, SLC1A1, and STARD5, which were found to potentially inhibit HCoV-229E, were not found to inhibit SCoV-2 (Zhao et al, 2022 ). These studies demonstrated overlap in ISG-mediated inhibition mechanisms of SCoV-2 and HCoV-229E replication.…”
Section: Resultsmentioning
confidence: 99%
“…We found a comparable level of similarity between the two genomes as well as in various pathways involved in pathogenesis and antiviral responses. Accordingly, the published literature suggests that the IFN-stimulated genes (ISGs) inhibit the infections with the two viruses in a similar fashion through overlapping pathways (Zhao et al, 2022 ). Supporting our hypothesis, some of the recent studies demonstrated the similarities in antiviral activities of pharmaceutical compounds against HCoV-229E and SCoV-2 (Siddell et al, 1983 ; Masters, 2006 ; Weiss and Leibowitz, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…These patients develop severe hypoxemia, which seems to be a trigger mechanism for damage in other organs, while for patients with sepsis, endothelial damage and coagulation activation are the classically well-described pathophysiological mechanisms related to the development of multiorgan failure. Cell populations of classical and non-classical monocytes have been demonstrated to be deeply involved in the immunopathogenesis of both systemic and organ (lung) hyper-inflammatory manifestations of severe COVID-19 [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…A SARS-CoV-2 egyik legfontosabb "fegyvere" tehát az, hogy eredményesen képes gátolni vagy legalábbis lassítani az I-es és III-as típusú IFN-válaszokat. A vírus patológiájának alapja jórészt ezen a "trükkön" alapul [7,8].…”
Section: öSszefoglaló Közleményunclassified